Hubungan Koping dan Kecemasan dengan Nyeri Post-ORIF Ekstremitas Bawah di RS Ortopedi Surakarta - Raharja, Muhammad Langlang Tahta; Widiastuti, Agung; Utomo, Endrat Kartiko (Pustaka Galeri Mandiri, 2025)
Lower extremity fractures are a significant musculoskeletal problem with a steadily increasing incidence globally and nationally. The standard treatment for fractures is ORIF. ORIF procedures cause postoperative pain, which is greatly influenced by psychological factors such as anxiety levels and the patient's coping mechanisms. Poorly managed post-ORIF pain can negatively impact physiological responses, emotional status, and slow down the patient's healing process. While pharmacological pain management remains a priority, there is still a need to integrate more optimal non-pharmacological interventions to address anxiety and pain at Prof. Dr. R. Soeharso Orthopedic Hospital in Surakarta, making an understanding of the relationships between these variables essential. This is a quantitative study with a descriptive correlational design and a cross-sectional approach. The study population includes all patients who have undergone lower extremity ORIF, with a sample of 35 respondents selected using purposive sampling techniques that meet the inclusion criteria. Data collection was conducted using standardized questionnaire instruments: the Jalowiec Coping Scale (JCS) to measure coping mechanisms, the Hamilton Anxiety Rating Scale (HARS) to assess anxiety levels, and the Numeric Rating Scale (NRS) to measure pain intensity. Data analysis utilized the Spearman Rank correlation test to test the hypothesis. The results of bivariate statistical analysis showed a significant relationship between coping mechanisms and pain intensity (p-value 0.002, r= -0.509) and between anxiety levels and pain intensity (p-value 0.000, r= 0.797) in patients who had undergone lower extremity ORIF. Conclusion: There is a relationship between coping mechanisms and anxiety levels with pain intensity in patients who have undergone lower extremity ORIF at Prof. Dr. R. Soeharso Orthopedic Hospital in Surakarta.